1899 Wyo. Sess. Laws 32-33, An Act for the Better Protection of the Game and Fish of this State . . . , ch. 19, § 14. - (:unkn) unknown (My University, 1899)
Allowed residents to receive hunting license for $1, non-residents to receive hunting license for $40.
Keywords: HUNTING REGULATION